1986
DOI: 10.1093/nar/14.10.4113
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of the murine dihydrofolate reductase transcription termination region: identification of a conserved DNA sequence element

Abstract: Structural features of the transcription termination region for the mouse dihydrofolate reductase gene have been determined and compared with those of several other known termination regions for protein coding genes. A common feature identified among these termination regions was the presence of a 20 bp consensus DNA sequence element (ATCAGAATATAGGAAAGTAGCAAT). The results imply that the 20 bp consensus DNA sequence element is important for signaling RNA polymerase II transcription termination at least in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Furthermore, no significant secondary structures could be deduced from the known sequence. Similar A-rich motifs have been identified in other transcription termination regions (Frayne & Kellems, 1986;Citron et al, 1984). Nuclear RNA from Ad2-infected cells contains a major 3' end that adjoins nt 620 of the termination region.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Furthermore, no significant secondary structures could be deduced from the known sequence. Similar A-rich motifs have been identified in other transcription termination regions (Frayne & Kellems, 1986;Citron et al, 1984). Nuclear RNA from Ad2-infected cells contains a major 3' end that adjoins nt 620 of the termination region.…”
Section: Discussionsupporting
confidence: 62%
“…This is probably due to limited translation of the unpolyadenylated CAT RNA. It is possible that upon deletion of a transcription termination element, transcription proceeds through the polyadenylation site (Frayne & Kellems, 1986) and a second element, such as that found in the human lymphokine gene GM-CSF (Shaw & Kamen, 1986) to generate an unstable mRNA. Although this possibility cannot be ruled out, it is unlikely that the deletion mutants pl to p6 and pl0 to p19 generate CAT mRNAs of near equal instability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments in other systems have provided evidence consistent with each of these ideas. In the h u m a n gastrin gene it appears that termination may occur at a single site (Back et al 1986;Sato et al 1986), whereas transcription of the mouse [3-globin (Citron et al 1984), dihydrofolate reductase (Frayne and Kellems 1986), and oL-amylase (Hagenbuchle et al 1984)probably occurs at multiple sites located within regions of several hundred base pairs. In contrast, no specific sites of termination have been detected during transcription of the polyoma virus late strand, and it has been suggested that termination of polyoma late transcription occurs at essentially random sites (Acheson 1984).…”
Section: Discussionmentioning
confidence: 99%